Kinetic Study on Ammonia-N Removal using Soil Mixed Culture - N., Zainol; Suryati, Mohd Mokhtar (Research India Publications, 2014)
Poultry manure wastewater contained high ammonia-N content. The ammonia-N is a very toxic substance that can cause mortality to poultry. An effective and economical solution to reduce ammonia-N in poultry manure wastewater is needed. The objective of this research was to determine the kinetic parameter for ammonia-N removal by using soil mixed culture (SMC). Ammonia-N was removed through nitrification process. Monod Model was used to represent nitrification process using SMC. Two types of SMC were utilized in this study namely, peat soil mixed culture (PS) and poultry farm soil mixed culture (PFS). There were two kinetic parameters determined from this study; maximum nitrification rate, k (h -1) and saturation constant, KN(mg/l). k value was representing the time taken for the ammonia-N to be reduced and K representing the reduced ammonia-N concentration. Kinetic parameters were determined using Linear Regression Method. k and KN values were calculated for both the PS and PFS. The kinetic constants for nitrification were determined as k=1.23 h-1 and KN=67.61 mg/l for PS and k=1.09 h and KN=68.454 mg/l for PFS. The values of k and K were representing the maximum reduction of ammonia-N concentration and the time taken for the process respectively. The kinetic constants could be applied as design parameter in scale-up process. PFS showed better performance in reducing the ammonia-N concentration compared to PS. It was founded that PFS removed ammonia-N at higher rate compared to PS. Comparison with other researchers showed that, the PFS from this study obtained better performance in ammoniaN removal rate.